Marx is Back, But Which One? On Knowledge Labour and Media Practice - Vincent Mosco (tripleC: Communication, Capitalism & Critique)
The global economic crisis has led to a resurgence of interest in the work of Karl Marx. This paper acknowledges this interest, but asks on which of the many shades of Marx, communication scholars should be focusing their research attention. The most general answer is all of Marx, from the early work on consciousness, ideology and culture, which has informed critical cultural studies through to the later work on the structure and dynamics of capitalism that provides bedrock for the political economy of communication. But there is particular need for communication scholars to pay more attention to work that does not fit so neatly in either of these foci, namely, Marx of the Grundrisse and Marx, the professional journalist. Communication scholars need to do so because we have paid insufficient attention to labour in the communication, cultural and knowledge industries. The Marx of these two streams of work provides important guidance for what I have called the labouring of communication as well as for addressing general problems in communication theory.